Exploring the English Language Education MPhil Scholars’ Adaptation to Blended Learning Modality (KMC Journal, 2025)
The blended modality of instruction integrates both traditional and digital online platforms. This study aims to explore the adaptability of English Language Education (ELE) scholars to the blended learning-based MPhil programme under the School of Education at a university in Nepal. The study employed a qualitative approach with an interpretive paradigm, utilizing phenomenology as a research design. Four participants were purposefully selected from the MPhil programme in the ELE second semester of 2024. To uphold the quality and ethical standards of the study, the participants were assigned pseudonyms. A semi-structured interview guideline served as the tool for the study. The interviews were recorded during formally organized Zoom meetings. I recorded and transcribed each interview individually and conducted a thematic analysis. The study results indicate that learners encounter challenges and issues in managing digital tools for e-learning platforms and rely on peer support and inquiries regarding portfolio creation and assessment systems. As the results reveal, blended learning proves beneficial for the diverse, heterogeneous, and dispersed learners at Mofussil, as it enhances their capabilities.